Experimental and numerical study on the shear-strain behavior of ballast with different gradations. - Venuja, S.; Navaratnarajah, S.K.; Bandara, C.S.; Jayasinghe, J.A.S.C. (Springer, 2023)
Rockﬁll materials are widely used in many infrastructure constructions including earth dams, rail tracks, retaining walls, highways, etc. The major role of these coarse granular materials is to stabilize the body of the structure and maintain the geometry. Ballast is one such material used primarily in rail track substructures. Several factors are governing the mechanical properties of the ballast layer such as particle size, shape, angularity, gradation, particle density, hardness, etc. Ballast gradations are varying from country to country based on geology, climatic condi- tion, source of parent rock, and economics. In Sri Lanka, biotite gneiss is used as the ballast material and there is no speciﬁc gradation for ballast. Further, the shear strength behaviour of the ballast is not fully understood with different gradations. Therefore, this study was carried out to analyse the effect of gradations on the shear behaviour of ballast using experimental and numerical analysis for Sri Lanka. Shear stress increased with normal stress increase due to the improved and intensiﬁed contact between particles. About 30% increase in shear stress was obtained from the laboratory test results for gradation with a high number of larger particles. Gener- ated numerical results showed a good acceptance of experimental results and led to carrying out a parametric study with different normal stresses. The ﬁndings of this study suggest that the presence of larger size particles causes higher friction which in turn results in an increase in shear strength.
Keywords: Ballast; Contact; Gradation; Mechanical properties; Shear Strength